Coexistence of Pituitary Adenoma and Primary Pituitary Lymphoma: A Case Report and Review of the Literature - Ren, Shangjun; Lu, Qingyang; Xiao, Yilei; Zhang, Yiming; Zhang, Lianqun; Li, Bin; Li, Mengyou (Frontiers in Surgery, 2022)
In the pituitary sella, collision tumors of pituitary adenoma and primary pituitary lymphoma are exceedingly rare. Here, we present a case of collision tumors of pituitary adenoma and primary pituitary lymphoma which was difficult to distinguish from other sellar region tumors. In addition, we systematically review the literature to find the characteristics of collision tumors of pituitary adenoma and lymphoma. It provides a new idea for the diagnosis and treatment of collision tumors of pituitary adenoma and lymphoma in the clinic.